2018
DOI: 10.1089/mdr.2017.0199
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Gene Detection in the Microbiome Context

Abstract: Within the past decade, microbiologists have moved from detecting single antibiotic resistance genes (ARGs) to detecting all known resistance genes within a sample due to advances in next generation sequencing. This has provided a wealth of data on the variation and relative abundances of ARGs present in a total bacterial population. However, to use these data in terms of therapy or risk to patients, they must be analyzed in the context of the background microbiome. Using a quantitative PCR ARG chip and 16S rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…All of the findings, as mentioned above, were also linked with positive correlations between the abundances of these opportunistic pathogens and human disease-related pathways in our study. Some previous studies have also reported multiple ARGs resided in these types of pathogenic bacteria [49,50], that maybe one of the critical reason for ARGs were more abundantly present in control samples.…”
Section: Opportunistic Pathogens Associated Human Disease-related Patmentioning
confidence: 86%
“…All of the findings, as mentioned above, were also linked with positive correlations between the abundances of these opportunistic pathogens and human disease-related pathways in our study. Some previous studies have also reported multiple ARGs resided in these types of pathogenic bacteria [49,50], that maybe one of the critical reason for ARGs were more abundantly present in control samples.…”
Section: Opportunistic Pathogens Associated Human Disease-related Patmentioning
confidence: 86%
“…Exposure to oxygen may have affected obligate anaerobic bacteria during sample collection and culture preparation. The genome of these bacteria could then have been present in the fecal samples, but the microorganism may not have been able to grow in culture [33]. The composition of culture media would also affect the community composition.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of culture media would also affect the community composition. For example, MCDA broth did not include short-chain fatty acids, which are required for the grown of some anaerobic bacteria like Roseburia [33]. In addition, some bacterial species may have faster growth rates in the selected culture conditions, which may favor them in the obtained CEM compared to bacteria with slower growth.…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge of the phenotypic outcomes of ARG expression and interactions in complex bacterial systems, such as the gut or urinary microbiome, is limited. This likely precludes optimal or safe clinical application of the generated results (19). More specifically, there is a need for further investigation into the characterization of the baseline bacteria and ARGs (both chromosomal and mobile elements) present in the resident microbiome.…”
mentioning
confidence: 99%
“…More specifically, there is a need for further investigation into the characterization of the baseline bacteria and ARGs (both chromosomal and mobile elements) present in the resident microbiome. This would allow us to better understand how ARGs are transferred bidirectionally between the commensal gut microflora and pathogenic species both naturally and under the lens of selective antibiotic pressure (19). Consequently, the "resistome" data obtained through NGS can be used to infer or predict phenotypic antibiotic resistance patterns.…”
mentioning
confidence: 99%